Effects of probiotics and its fermented milk on constipation: a systematic review - Jiaming Yan; Meiling Wu; Wei Zhao; Lai-Yu Kwok; Wenyi Zhang (Food Science and Human Wellness)
This study reviewed clinical evidence of probiotics-mediated effects on constipation. Four databases were used in the literature searches, namely Cochrane Library, Embase, Pubmed, and Web of Science. The last retrieval time was March 2021. Collected data were analyzed by Review Manager (version 5.3) and Stata (version 14). The primary search retrieved 8 418 articles after removing duplicates. Eventually, twenty six studies were included in the meta-analysis. Administration of probiotics significantly increased stool frequency (MD: 1.15 times/week; 95 % CI: 0.59 to 1.70; P < 0.000 1), improved bloating (MD: –0.48; 95 % CI: –0.89 to –0.07; P = 0.02), reduced abdominal pain (MD: –0.71; 95 % CI: –1.25 to –0.16; P = 0.01), and improved quality of life (MD: –0.73; 95 % CI: –1.37 to –0.10; P = 0.02). However, the clinical effect of intake of probiotics on stool consistency was non-significant (MD: 0.07; 95 % CI: –0.34 to 0.48; P = 0.73). Based on our analysis, probiotic supplements were effective in relieving constipation through symptom improvement. The effectiveness of dosage forms of intervention ranked: capsules > others (tablets, powder) > fermented milk.